English (ARTEKS : Jurnal Teknik Arsitektur, 2025)
One of the most tangible aspects of Southern Fujianese culture is its traditional architecture, known for its vibrant colors, ornate designs, and exaggerated forms. Despite its cultural significance, appreciation for heritage architecture has declined over the decades. In Malaysia, many Hokkien heritage buildings reflect a blend of traditional Chinese, colonial, and local Malay architectural influences. However, there is limited research on how Hokkien architectural components contribute to sustainability. This paper addresses this gap by examining sustainable elements in Hokkien architecture, particularly in the Peranakan-style Blue Mansion (Cheong Fatt Tze). The study analyses architectural features such as the gable roof structure, ridge beasts, and decorative “Chien Nien” and “Chai Hui” on the façade to understand their role in achieving sustainability. Data collected through case studies and site observations at the Blue Mansion are discussed, highlighting how these components contribute to architectural sustainability. This research is crucial as it delves into the sustainable aspects of Hokkien architecture within a Peranakan context, providing insights into Fujian’s cultural heritage and its application in sustainable design.